BRAND STRATEGY FORMATION IN THE CONDITIONS OF TRANSFORMATION OF CONSUMER SENTIMENTS OF UKRAINIAN SOCIETY - Ягельська, Катерина; Василишина, Любов (SWorldJournal, 2023)
The article describes the brand strategy as an economic category. The main brand strategies are systematized according to subject characteristics. The main factors of brand strategy formation are considered and the content of consumer attitudes is reveal